2020
DOI: 10.1080/1828051x.2020.1790045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial fermentation processing of sesame meal and enzyme supplementation on broiler performances

Abstract: Two experiments were conducted to investigate the effects of fermented sesame meal (FSM) replacement by soybean meal (SBM) in broilers. In the first experiment, a completely randomised design with 3 Â 4 factorial arrangement was used for microorganism comparison [Lactobacillus acidophilus (LA), Saccharomyces cerevisiae (SC) and LA þ SC] and fermentation time courses (0, 2, 7, and 12 days). In the second experiment, a total of 420-day-old boilers (Ross 308V R ) were randomly allocated to seven treatments and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…In this study, broiler chicks fed the diet supplemented with S. pombe expressed phytase increased the AID of calcium ( p = 0.036) and phosphorus ( p = 0.045), but did not affect the crude protein (Table 3 ), which was affirmed by the study of Hajimohammadi et al. ( 2020 ). In brief, dietary supplementation of 250 and 500 FTU/kg S. pombe expressed phytase could degrade phytate, which was manifested in the increase of the AID of phosphorus and calcium.…”
Section: Resultssupporting
confidence: 74%
“…In this study, broiler chicks fed the diet supplemented with S. pombe expressed phytase increased the AID of calcium ( p = 0.036) and phosphorus ( p = 0.045), but did not affect the crude protein (Table 3 ), which was affirmed by the study of Hajimohammadi et al. ( 2020 ). In brief, dietary supplementation of 250 and 500 FTU/kg S. pombe expressed phytase could degrade phytate, which was manifested in the increase of the AID of phosphorus and calcium.…”
Section: Resultssupporting
confidence: 74%
“…Earlier studies have proved that feeding broiler chicks with phytase-containing diet could improve their growth performance [ 29 , 30 ] which agrees with the findings of the present study. The mechanism of phytase supplementation improving growth performance of broiler chicks was related to the event of phytate hydrolysis by phytase, which releases the phytate-bound nutrient ingredients [ 31 , 32 ], thus improving nutrient digestibility and resulting in a decrease of FCR and an increase of BWG in birds [ 5 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be predicted because the increase of carcass weight was related to the increase of body weight, a higher body weight corresponds to a higher carcass weight [ 48 ]. Similarly, several studies have reported that feeding broiler chicks with phytase-containing diet improved body weight, thus leading to a higher carcass weight [ 34 , 48 , 49 ]. However, dietary supplementation of phytase did not affect the relative weight of breast weight, liver, bursa of fabricius, abdominal fat, spleen, and gizzard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations